Study on the Influence of Steam Injection Mode Difference on the Heat Transfer Behavior of Wellbore Steam Circulation Electric Heating - Feng, Haiyang; Dong, Liangliang; Zhou, Chao (Scientific Journal of Technology, 2026)
Aiming at the problem of insufficient understanding of the influence of different steam injection methods on the heat transfer law of wellbore steam circulation electric heating in SAGD technology for heavy oil thermal recovery, based on the theory of heat transfer and fluid mechanics, this paper establishes a numerical calculation model of wellbore steam circulation electric heating to simulate the process of electric heating and steam synergistic heat transfer in horizontal steam injection wells. The difference of temperature field distribution between wellbore and electric heater of short tube steam injection, double tube steam injection and long tube steam injection was studied. The results show that the heating effect of short tube steam injection on steam is weaker than that of long tube steam injection, and the temperature of electric heater is higher. It is necessary to cooperate with high steam injection speed or low power density operation to avoid overtemperature. The heating effect of double-tube steam injection is similar to that of long-tube steam injection under the condition of halving steam injection volume. The temperature overrun of heater can be improved by increasing steam injection volume, reducing power density and optimizing steam distribution ratio. The research work in this paper provides a theoretical basis for the optimization of steam injection mode and heat transfer law in the process of electric heating assisted development of heavy oil SAGD technology.